Appointment in Apollonia - Potts, Daniel T. (Anabasis. Studia Classica et Orientalia, 2017)
In Book 5 of the Histories Polybius, our only extant source, describes the rebellion of Molon, the Seleucid satrap of Media, in 222 BC. After forcing one of Molon’s generals to raise the siege of a place called Dura, Antiochus III and his army, hoping to intercept Molon en route from Seleucia-on-the-Tigris to Media, marched ‘continuously for eight days’, after which ‘they crossed the mountain called Oreicon and arrived at Apollonia’, near which the final battle and defeat of Molon occurred (Polybius, Hist. 5.52). The present article traces itinerary of this campaign and the principal places involved: Dura, the Oreicon mountain and Apollonia.